2019
DOI: 10.1016/j.fertnstert.2019.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Association between diminished ovarian reserve and luteal phase deficiency

Abstract: Objective: To determine the association between biomarkers of ovarian reserve and luteal phase deficiency (LPD). Design: Secondary analysis of a prospective time-to-conceive cohort study. Setting: Not applicable. Patient(s): Women attempting conception, aged 30-44 years, without known infertility. Intervention(s): Measurement of early follicular phase serum levels of antim€ ullerian hormone, FSH, inhibin B, and E 2. Main Outcome Measure(s): The primary outcome was LPD, defined by luteal bleeding (LB) (R1 day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…DOR is characterized with the loss of ovarian normal reproductive potential. 18,19 The condition is a high morbidity syndrome of women with normal aging and may results in decreased ovarian response, low pregnancy rates and poor IVF outcomes. 20 Previous study showed that smoking, toxic chemicals, radiation, environmental and genetic change, endometriosis and ovarian surgery may lead to DOR, but the cause was still unknown in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…DOR is characterized with the loss of ovarian normal reproductive potential. 18,19 The condition is a high morbidity syndrome of women with normal aging and may results in decreased ovarian response, low pregnancy rates and poor IVF outcomes. 20 Previous study showed that smoking, toxic chemicals, radiation, environmental and genetic change, endometriosis and ovarian surgery may lead to DOR, but the cause was still unknown in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…Even though age-related decrease in the uterine and placental function were also described in some women, ART outcomes of aging women obtained with the use of oocytes from young donors are excellent [ 50 ], suggesting that uterine aging only represents a marginal problem in humans. Moreover, in a large cohort study, and after adjusting for age, no significant association between DOR and a short luteal phase was detected [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand some studies described age-unrelated problems of uterine receptivity leading to recurrent implantation failure (RIF). RIF usually refers to failure to achieve a clinical pregnancy after transfer of at least four good-quality embryos in a minimum of 3 fresh or frozen cycles in woman under the age of 40 years [ 51 , 52 ]. There is little information about the possible role of oxidative stress in the etiology of RIF.…”
Section: Resultsmentioning
confidence: 99%
“…Infertility affects a significant proportion of humanity and is regarded as a global public health issue by the World Health Organization (1,2). Diminished ovarian reserve (DOR), defined as a reduction in both oocyte quality and quantity, is one of the most common causes of female infertility and poor ovarian response to controlled ovarian stimulation with a rapidly increasing occurrence rate (3,4). In addition, women with DOR have exceedingly high rates of recurrent pregnancy loss and no euploid embryos (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%